On \(α\)-Continuity in Intuitionistic Topological Spaces (Journal of Informatics and Mathematical Sciences, 2017)
The aim of this paper is to explore intuitionistic \(α\)-continuity and obtain their characteristics.
Keywords: \(α\)-Continuity; Intuitionistic Topological Spaces